A comparison of young star properties with local galactic environment for LEGUS/LITTLE THINGS dwarf irregular galaxies - Hunter, Deidre A.; Gouliermis, Dimitrios A.; Grebel, Eva K. (The astronomical journal, 2018)
We have explored the role environmental factors play in determining characteristics of young stellar objects in nearby dwarf irregular and blue compact dwarf galaxies. Star clusters are characterized by concentrations, masses, and formation rates; OB associations by mass and mass surface density; O stars by their numbers and near-ultraviolet absolute magnitudes; and H ii regions by Hα surface brightnesses. These characteristics are compared to surrounding galactic pressure, stellar mass density, H i surface density, and star formation rate (SFR) surface density. We find no trend of cluster characteristics with environmental properties, implying that larger-scale effects are more important in determining cluster characteristics or that rapid dynamical evolution erases any memory of the initial conditions. On the other hand, the most massive OB associations are found at higher pressure and H i surface density, and there is a trend of higher H ii region Hα surface brightness with higher pressure, suggesting that a higher concentration of massive stars and gas is found preferentially in regions of higher pressure. At low pressures we find massive stars but not bound clusters and OB associations. We do not find evidence for an increase of cluster formation efficiency as a function of SFR density. However, there is an increase in the ratio of the number of clusters to the number of O stars with increasing pressure, perhaps reflecting an increase in clustering properties with SFR.